scRNA-seq of gastric tumor shows complex intercellular interaction with an alternative T cell exhaustion trajectory - Keyong Sun; Runda Xu; Fuhai Ma; Naixue Yang; Yang Li; Xiaofeng Sun; Peng Jin; Wenzhe Kang; Lemei Jia; Jianping Xiong; Haitao Hu; Yantao Tian; et al. (Nature Communications, 2022)
Gastric cancer can vary in tumour stage and immune cell involvement. Here the authors compare gene expression in immune cell types from the blood and the tumour site from GC patients using single cell and TCR sequencing and show that IL17 + CD8 + T cells have a phenotype related to that seen with exhausted cells.